Kerala: Temples and World-Class Universities - Altbach, Philip (International Higher Education, 2012)
A Hindu temple in the south Indian state of Kerala has located treasure work several billion dollars in its basement. This article proposes uses some of that money to build a world-class research university in Kerala to help boost its knowledge economy.